Translation Error Taxonomies in Indonesian Tourism Guidebooks - Sumiati , Ati; Laksana, Andhika; Noverino, Romel (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2021)
There are many tourism guidebooks spread all around Indonesia yet they are not of good quality. This study embarks on the idea that the quality of tourism guidebook is still far from perfect. This study intends to explore the type of error taxonomies found in the tourism guidebooks by employing qualitative method. Six tourism guidebooks were collected and used as data and the theory being used is proposed by Dastjerdi and Abdolmaleki (2012). They modify the classification of errors in translation based on Keshavarz and ATA and proposed the name of error taxonomy. This error taxonomy has four major error types of syntactic error with three error patterns, semantic errors with 12 error patterns, pragmatic errors with 4 patterns, and translation-specific errors with 4 patterns. The selected guidebooks are then analyzed sentence by sentence using the error taxonomy in order to find out the error in the translation. Total data gathered are 519 with 292 are recognized as errors. These are then broken down into four types of errors: semantic errors having 149 errors (51%), syntactic errors having 133 errors (45%), and the least occurrence of errors is in the type of both pragmatic and translation-specific errors with only 5 errors (2%). This result will provide recommendation for the tourism boards or the local government who published these guidebooks to take prompt action to review and revise their edition of tourism guidebooks.